Novel aspects of the reactions of hydrogenases with small molecule inhibitors - Wait, A; Annemarie Wait (2011)
Hydrogenases catalyse the reversible oxidation and production of H₂. They have been the subject of intense interest in recent years since these enzymes, or catalysts inspired by them, may greatly enhance our exploitation of H₂ as an energy carrier in a future ‘green’ H₂-based economy. However, a major challenge to the future use of these catalysts is their reactions with small molecule inhibitors, such as O₂ or CO. This thesis presents studies using Protein Film Electrochemistry, in which an enzyme is adsorbed onto an electrode to give an electroactive film. Although most hydrogenases are inhibited or irreversibly damaged by even trace O₂, certain O₂-tolerant hydrogenases are unusual in that they are able to sustain H₂ oxidation activity in the presence of O₂. Results outlined in this thesis suggest that the O₂ tolerance of the membrane-bound [NiFe]-hydrogenase from Ralstonia eutropha relies upon O₂ attack generating exclusively the ‘Ready’ inactive state (formed by complete, four-electron reduction of O₂), which subsequently reactivates both rapidly and at high potential. The results contributed to a new explanation for how hydrogenases in certain microbes survive O₂. Electrochemical studies performed on a variant enzyme suggest that a modified proximal FeS cluster plays a role in conferring this O₂ tolerance. Studies of an enzymatic H₂/O₂ fuel cell employing the O₂-tolerant [NiFe]-hydrogenase Hyd1 from Escherichia coli as the anodic catalyst highlight the subtle influence of the reactions of the hydrogenase with O₂ on the power characteristics of the fuel cell under various operating conditions. This research also identifies straight-chain aldehydes as unprecedented inhibitors of H₂ production by the [FeFe]-hydrogenases. However, some of these results cannot currently be made freely available as they are to be published at a later date in academic journals.